Analisis kesiapan kerja siswa SMK keperawatan: Peran prestasi, kompetensi prakerin, dan motivasi kerja - Kun Arifah (Piramida Akademi, 2025)
The aim to be achieved in this research is to find out (1) the influence of learning achievement, Prakerin competence, and work motivation on the work readiness of class XII students of the Health Vocational School Nursing Skills Program in Gunungkidul Regency; (2) the influence of learning achievement on the work readiness of class XII students of the Nursing Skills Program at the Health Vocational School in Gunungkidul Regency; (3) the influence of Prakerin competence on the work readiness of class XII students of the Health Vocational High School Nursing Skills Program in Gunungkidul Regency; (4) the effect of work motivation on work readiness of class XII students of the Health Vocational School Nursing Skills Program in Gunungkidul Regency. This research is a correlational study using a quantitative data approach. The population in this study were all students of class XII Nursing Skills Program at the Health Vocational School in Gunungkidul Regency a total of 131 students. The sampling technique in this study is total sampling. The data collection techniques used in this research are: (1) documentation for variable data on learning achievement and Prakerin competence; (2) questionnaire for data on work motivation and work readiness variables. The conclusion of the research shows that together learning achievement, Prakerin competence, and work motivation greatly determine students' work readiness; students' work readiness can be improved by increasing learning achievement, Prakerin competence and students' work motivation. Meanwhile, individually, learning achievement will determine students' work readiness; the higher the learning achievement, the higher the student's work readiness, and vice versa. Prakerin competence also determines students' work readiness; the higher the Prakerin competency, the higher the student's work readiness, and vice versa. Likewise, work motivation determines student work readiness; the higher the work motivation, the higher the student's work readiness, and vice versa.